Methylglyoxal Impairs Insulin Secretion of Pancreatic β-Cells through Increased Production of ROS and Mitochondrial Dysfunction Mediated by Upregulation of UCP2 and MAPKs - Jinshuang Bo; Shiya Xie; Yi Guo; Chunli Zhang; Yanming Guan; Chunmei Li; Jianxin Lu; Qing H. Meng (Journal of Diabetes Research)
Methylglyoxal (MG) is a highly reactive glucose metabolic intermediate and a major precursor of advanced glycation end products. MG level is elevated in hyperglycemic disorders such as diabetes mellitus. Substantial evidence has shown that MG is involved in the pathogenesis of diabetes and diabetic complications. We investigated the impact of MG on insulin secretion by MIN6 and INS-1 cells and the potential mechanisms of this effect. Our study demonstrates that MG impaired insulin secretion by MIN6 or ISN-1 cells in a dose-dependent manner. It increased reactive oxygen species (ROS) production and apoptosis rate in MIN6 or ISN-1 cells and inhibited mitochondrial membrane potential (MMP) and ATP production. Furthermore, the expression of UCP2, JNK, and P38 as well as the phosphorylation JNK and P38 was increased by MG. These effects of MG were attenuated by MG scavenger N-acetyl cysteine. Collectively, these data indicate that MG impairs insulin secretion of pancreatic β-cells through increasing ROS production. High levels of ROS can damage β-cells directly via JNK/P38 upregulation and through activation of UCP2 resulting in reduced MMP and ATP production, leading to β-cell dysfunction and impairment of insulin production.